Parietal-hippocampal rTMS improves cognitive function in Alzheimer's disease and increases dynamic functional connectivity of default mode network. (September 2022) - Wei, Lili; Zhang, Yingchun; Wang, Jintao; Xu, Luoyi; Yang, Kehua; Lv, Xinghui; Zhu, Zhenwei; Gong, Qian; Hu, Weiming; Li, Xia; Qian, Mincai; Shen, Yuedi; et al.
Highlights: A double-blind, randomized, sham-controlled, fMRI-guided rTMS trial. Individualized rTMS over the parietal region is effective in treating Alzheimer's disease. fMRI-guided rTMS treatment improves patients' cognitive performance. fMRI-guided rTMS treatment enhances functional connectivity of DMN. IMPROVED cognitive function is related to enhanced DMN functional connectivity. Abstract: Parietal-hippocampal repetitive transcranial magnetic stimulation (rTMS) improves cognitive function in Alzheimer's disease (AD), however, the underlying therapeutic mechanism has not been elucidated. A double-blind, randomized, sham-controlled parietal-hippocampal rTMS trial (five sessions/week for a total of 10 sessions) of mild-to-moderate AD patients was conducted in the study. High-frequency rTMS was applied to a subject-specific left lateral parietal region with the highest functional connectivity with the hippocampus based on resting-state fMRI. A multimodal MRI scan and a complete neuropsychological battery of tests were conducted at baseline, immediately after the intervention and 12-week follow-up after the rTMS treatment. Compared to sham treatment ( n  = 27), patients undergoing active rTMS treatment ( n  = 29) showed higher Mini Mental State Examination (MMSE) score and dynamic functional connectivity (dFC) magnitude of the default mode network (DMN) after two weeks of rTMS treatment, but not at 12-week follow-up. A significant positive correlation was observed between changes in MMSE and changes in the dFC magnitude of DMN in patients who underwent active-rTMS treatment, but not in those who received sham-rTMS treatment. The findings of the current study indicate that fMRI-guided rTMS treatment improves cognitive function of AD patients in the short term, and DMN functional connectivity contributes to therapeutic effectiveness of rTMS.